Hyporesponse to statin therapy among patients with acute coronary syndrome: prevalence, impact on the development of heart failure in a short-term follow-up - I. V. Druk; O. Yu. Korennova; Yu. E. Yukhina; M. V. Savchenko; N. A. Maciyauskas; L. V. Shukil (Российский кардиологический журнал, 2022)
Aim. To study the prevalence of hyporesponse to statin therapy and its impact on the development of heart failure (HF) among patients after acute coronary syndrome (ACS) in a short-term follow-up.Material and methods. This retrospective analysis of outpatient medical records of 400 patients observed at the Omsk Clinical Cardiology Dispensary after ACS was carried out. Optimal medication therapy was prescribed as part of the preferential provision of medicines under the 1H Program, including high-dose atorvastatin therapy (80 mg/day). Low-density lipoprotein cholesterol (LDL-C) was assessed at baseline and 1 and 12 months after therapy. Hyporesponse to statins was defined as the percentage reduction in LDL-C 14; left atrial volume index >34 ml/m2) function.Results. There were 107 patients with hyporesponse (26,8%). Depending on the initial response to therapy, patients were divided into two groups: group 1 (hyporesponse, n=107), group 2 (more pronounced response, n=293). After 1 month, patients in the hyporesponse group had a higher level of LDL-C — 2,4 [2,2; 2,9] mmol/l (Me [25; 75%]) vs 2,0 [1,7; 2,5] mmol/l (p>0,05) in the second group. There was no difference in the prevalence of hospitalizations for recurrent ACS in the compared groups, as well as in the prevalence of new HF cases between groups.Conclusion. The prevalence of hyporesponse to statin therapy was 26,8%, which required correction of lipid-lowering therapy in order to prevent recurrent cardiovascular events. Given the pleiotropic effects of statins that can participate in HF pathogenesis, as well as the inconsistency of current research results, further prospective long-term studies are required.